2015
DOI: 10.1111/dar.12308
|View full text |Cite
|
Sign up to set email alerts
|

Injecting buprenorphine‐naloxone film: Findings from an explorative qualitative study

Abstract: Understanding knowledge acquisition about injecting new formulations of opioid substitution therapy is crucial in developing more effective harm-reduction strategies. Dissemination by peer networks to those who are currently or planning to inject BNX film regarding the 'gelatine like' texture when mixing, using only cold water and double filtering is important to ensure safer injecting practices. Findings from this study highlight the importance of peer networks for the dissemination of harm-reduction informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The volume of buprenorphine arrests, especially for trafficking, might appear concerning, particularly due to its primary indication for the treatment of individuals who are addicted to opioids in conjunction with reports of misuse . We postulate that although buprenorphine may be used for euphoria in some buprenorphine‐naive patients, most buprenorphine is being used in those who are self‐treating symptoms of withdrawal in the context of an opioid use disorder; therefore, our data illustrate the need for increased access to prescribed and monitored buprenorphine therapy and associated psychosocial treatments.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The volume of buprenorphine arrests, especially for trafficking, might appear concerning, particularly due to its primary indication for the treatment of individuals who are addicted to opioids in conjunction with reports of misuse . We postulate that although buprenorphine may be used for euphoria in some buprenorphine‐naive patients, most buprenorphine is being used in those who are self‐treating symptoms of withdrawal in the context of an opioid use disorder; therefore, our data illustrate the need for increased access to prescribed and monitored buprenorphine therapy and associated psychosocial treatments.…”
Section: Discussionmentioning
confidence: 83%
“…The volume of buprenorphine arrests, especially for trafficking, might appear concerning, particularly due to its primary indication for the treatment of individuals who are addicted to opioids 11 in conjunction with reports of misuse. 2,3 We postulate that although buprenorphine may be used for euphoria in some buprenorphine-naive patients, most buprenorphine is being used in those who are self-treating symptoms of withdrawal in the context of an opioid use disorder; therefore, our data illustrate the need for increased access to prescribed and monitored buprenorphine therapy and associated psychosocial treatments. Because buprenorphine was responsible for almost all Schedule III arrests and the second highest prescription drug, behind only oxycodone, for drug arrests in the first quarter of 2016, naltrexone extendedrelease injectable suspension, in addition to buprenorphine, should be considered for preferred drug status by private and state health insurance plans.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The most common method for parenteral abuse is to dissolve the strips in a variable amount of water, filter the solution, and then inject the medication intravenously. 12 In recent years, the hand surgery team at the University of Kentucky Medical Center has noted an increasing number of patients presenting to the emergency room or outpatient clinics with ischemia of the hand and digits after inadvertent or intentional intra-arterial injection of sublingual BNX. When looking to the literature for guidance on the management of these patients, we found that very little had been written about these injuries.…”
Section: Hand 12(5)mentioning
confidence: 99%
“…The opioid partial agonist buprenorphine is a critical component of medication-assisted treatment for opioid use disorder and is associated with improved treatment adherence and decreased illicit opioid use ( 1 ). Combination buprenorphine/naloxone transmucosal products are designed to deter injection owing to the opioid-antagonist actions of naloxone and can reduce the desired effects and precipitate rapid withdrawal when these products are administered intravenously; nonetheless, injection of transmucosal buprenorphine/naloxone has been reported ( 2 , 3 ). During 2016–2017, 14.6% of approximately 127,000 emergency department (ED) visits for nonmedical use * of prescription opioids involved buprenorphine products, commonly for injection-related complications ( 4 ).…”
mentioning
confidence: 99%